Impact of Newborn Screening on Adult Height in Patients With Congenital Adrenal Hyperplasia (CAH) - Hoyer-Kuhn, Heike; Eckert, Alexander J.; Binder, Gerhard; Bonfig, Walter; Dübbers, Angelika; Riedl, Stefan; Wölfle, Joachim; Dörr, Helmuth-Günther; Holl, Reinhard W. (Journal of Clinical Endocrinology and Metabolism, 2023)
CONTEXT: Treatment of children with classical congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency is challenging. Linear growth and adult height are compromised according to recent publications. However, most of these data were obtained in the era before CAH newborn screening. DESIGN: Body height of patients with classical CAH diagnosed before and after the establishment of newborn screening were analyzed retrospectively. PATIENTS AND METHODS: We identified 600 patients with classical CAH (227 male) with data on near-adult height (NAH), target height (TH), and information on newborn screening from the electronic German CAH registry (German Society for Paediatric Endocrinology and Diabetology). Newborn screening was performed in 101 (16.8%) patients. All patients received hydrocortisone with or without fludrocortisone.To assess the effects of newborn screening, a linear regression model adjusted/stratified for sex and phenotype was used (SAS 9.4). RESULTS: TH corrected NAH (mean; 95% confidence interval) was closer to 0 in patients with CAH and newborn screening [-0.25 standard deviation score (SDS); -0.44 to -0.06] than in patients without newborn screening (-0.44 SDS; -0.52 to -0.36) (P = .069). Screening had no effect on NAH in female patients. In male patients, NAH was significantly better (P = .033) with screening than without screening. After stratifying for CAH phenotype, screening did not affect the NAH of patients with salt-wasting CAH. Patients with simple-virilizing CAH had a significantly better cNAH (P = .034) with screening (0.15 SDS; -0.28-0.59) than without screening (-0.35 SDS; -0.52 to -0.18). CONCLUSIONS: Our data suggest that newborn screening might be associated with improved NAH in male CAH patients and in patients with simple-virilizing CAH.
CRIS-Team Scopus Importer:2023-11-03
Keywords: congenital adrenal hyperplasia; CYP21A2; near adult height; newborn screening